Bacterial community profiles within the water samples of Leptospirosis outbreak areas - Asmalia Md Lasim; Ahmad Mohiddin Mohd Ngesom; Sheila Nathan; Fatimah Abdul Razak; Mardani Abdul Halim; Wardah Mohd Saleh; Kamaruddin Zainul Abidin; Farah Shafawati MohdTaib (Journal for life and environment, 2024)
Background: Leptospirosis is a water-related zoonotic disease. The disease is primarily transmitted from animals to humans through pathogenic Leptospira bacteria in contaminated water and soil. Rivers have a critical role in Leptospira transmissions, while co-infection potentials with other waterborne bacteria might increase the severity and death risk of the disease. Methods: The water samples evaluated in this study were collected from four recreational forest rivers, Sungai Congkak, Sungai Lopo, Hulu Perdik, and Gunung Nuang. The samples were subjected to next-generation sequencing (NGS) for the 16S rRNA and in-depth metagenomic analysis of the bacterial communities. Results: The water samples recorded various bacterial diversity. The samples from the Hulu Perdik and Sungai Lopo downstream sampling sites had a more significant diversity, followed by Sungai Congkak. Conversely, the upstream samples from Gunung Nuang exhibited the lowest bacterial diversity. Proteobacteria, Firmicutes, and Acidobacteria were the dominant phyla detected in downstream areas. Potential pathogenic bacteria belonging to the genera Burkholderiales and Serratia were also identified, raising concerns about co-infection possibilities. Nevertheless, Leptospira pathogenic bacteria were absent from all sites, which is attributable to its limited persistence. The bacteria might also be washed to other locations, contributing to the reduced environmental bacterial load. Conclusion: The present study established the presence of pathogenic bacteria in the river ecosystems assessed. The findings offer valuable insights for designing strategies for preventing pathogenic bacteria environmental contamination and managing leptospirosis co-infections with other human diseases. Furthermore, closely monitoring water sample compositions with diverse approaches, including sentinel programs, wastewater-based epidemiology, and clinical surveillance, enables disease transmission and outbreak early detections. The data also provides valuable information for suitable treatments and long-term strategies for combating infectious diseases.